2011
DOI: 10.1016/j.tips.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

New advances in NMDA receptor pharmacology

Abstract: N-Methyl-D-aspartate (NMDA) receptors are tetrameric ion channels containing two of four possible GluN2 subunits. These receptors have been implicated for decades in neurological diseases such as stroke, traumatic brain injury, dementia, and schizophrenia. The GluN2 subunits contribute substantially to functional diversity of NMDA receptors and are distinctly expressed in development and among brain regions. Thus, subunit-selective antagonists and modulators that differentially target the GluN2 subunit might p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
170
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 71 publications
4
170
0
1
Order By: Relevance
“…NMDARs non-selectively, whereas the GluN2A subunit is antagonized by the competitive antagonist NVP-AAM077, which was further demonstrated to have a better selectivity for the GluN2D subunit; the GluN2B subunit is also selectively blocked by the non-competitive antagonists ifenprodil and Ro 25-6981, among others (reviewed by Ogden and Traynelis, 2011). Recently, TCN201 was described as a potent GluN2A…”
Section: + and Mk-801 Are Channel Blockers And D-apv Is A Competitivmentioning
confidence: 99%
“…NMDARs non-selectively, whereas the GluN2A subunit is antagonized by the competitive antagonist NVP-AAM077, which was further demonstrated to have a better selectivity for the GluN2D subunit; the GluN2B subunit is also selectively blocked by the non-competitive antagonists ifenprodil and Ro 25-6981, among others (reviewed by Ogden and Traynelis, 2011). Recently, TCN201 was described as a potent GluN2A…”
Section: + and Mk-801 Are Channel Blockers And D-apv Is A Competitivmentioning
confidence: 99%
“…The GluN2 subunits therefore determine the physiological roles of NMDA receptor subtypes, and, for this reason, they have received considerable interest as potential therapeutic targets. To this end, ligands that distinguish NMDA receptor subtypes based on GluN2 subunits are desirable due to their obvious utility as pharmacological tools and as potential therapeutic agents for the treatment of CNS disorders (7,8).…”
mentioning
confidence: 99%
“…Considerable progress has been made in the development of subunit-selective allosteric modulators (7)(8)(9)(10)(11)(12)(13), but the development of subtype-selective competitive NMDA receptor antagonists has been less successful. The competitive glutamate-site antagonist NVP-AAM077 (hereafter NVP) was originally reported to have 100-fold preference for GluN1/2A over GluN1/2B (14).…”
mentioning
confidence: 99%
“…HAD contributes to functional deficits such as learning and memory decline, cognitive and reasoning dysfunction, inattention, impaired motor skills, and abulia, among others (Singer et al, 2010;Rosca et al, 2012;Peluso and Spudich 2014). More importantly, gp120 can activate macrophages resulting in the production of copious amounts of chemokines/cytokines, and can also influence glutamate uptake in astrocytes and interfere with the glutamine supply for neurons, severely impacting learning and memory (Hazleton et al, 2010;Ogden and Traynelis 2011;Fields et al, 2014). Through behavioral testing in the first week, we found that the average escape latency and number of errors in gp120-treated groups were higher than those of Ctrl rats, indicating that gp120 affected learning and memory in rats.…”
Section: Discussionmentioning
confidence: 99%